2019
DOI: 10.1007/s00167-019-05382-w
|View full text |Cite
|
Sign up to set email alerts
|

Humeral head resurfacing is associated with less pain and clinically equivalent functional outcomes compared with stemmed hemiarthroplasty at mid-term follow-up

Abstract: Purpose Humeral head resurfacing (HHR) is a less invasive, anatomic alternative to the conventional stemmed hemiarthroplasty in patients in whom isolated humeral head replacement is preferred. It was hypothesized that, in a mid-term crosssectional subjective outcome analysis, HHR would have equivalent patient-reported and functional outcomes to stemmed hemiarthroplasty (HA). Methods A total of 213 HHR and 153 HA procedures were performed at a single academic institution from 2000 to 2014. Of these, 106 HHR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Included studies [39,40,[45][46][47][48]] that compared outcomes between RHA and SHA were included in this meta-analysis. The search strategy through the PRISMA flow diagram is detailed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Included studies [39,40,[45][46][47][48]] that compared outcomes between RHA and SHA were included in this meta-analysis. The search strategy through the PRISMA flow diagram is detailed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [45][46][47][48] reported postoperative range of motion, but only two studies [45,46] with homologous data could be combined to assess the degree of forward flexion and external rotation. The degree of internal rotation could not be calculated due to insufficient data.…”
Section: Range Of Motion and Pain Scorementioning
confidence: 99%
See 3 more Smart Citations